Assistant platforms - Rainer Schmidt; Rainer Alt; Alfred Zimmermann (Electronic Markets, 2023)
Many assistant systems have evolved toward assistant platforms. These platforms combine a range of resources from various actors via a declarative and generative interface. Among the examples are voice-oriented assistant platforms like Alexa and Siri, as well as text-oriented assistant platforms like ChatGPT and Bard. They have emerged as valuable tools for handling tasks without requiring deeper domain expertise and have received large attention with the present advances in generative artificial intelligence. In view of~ their growing popularity, this Fundamental outlines the key characteristics and capabilities that define assistant platforms. The former comprise a multi-platform architecture, a declarative interface, and a multi-platform ecosystem, while the latter include capabilities for composition, integration, prediction, and generativity. Based on this framework, a research agenda is proposed along the~capabilities and affordances for assistant platforms.
Keywords: L14; L15; L22; M15; O30; 620; Digital platforms; Ecosystems; Generative artificial intelligence (GAI); Virtual assistants; Multi-platform